Biodegradable derivatives of tranexamic acid as transdermal permeation enhancers - Vávrová, Katerina; Hrabálek, Alexandr; Dolezal, Pavel; Holas, Tomás; Klimentová, Jana (Journal of controlled release, 2005)
The purpose of this work was to develop a novel approach to transdermal permeation enhancer design, based on utilizing some favorable properties of their metabolites. As an example of this concept, a series of carbamic acid salts of tranexamic acid (TXA) esters was synthesized, because TXA was previously shown to improve skin barrier homeostasis. Enhancement activities of 1% TXA derivatives dispersed in both hydrophilic and lipophilic vehicles were evaluated in vitro using human skin and theophylline as a model drug. Dispersed in an aqueous donor vehicle, the dodecyl ester showed the enhancement ratio (ER) of 4.3+/-0.9, which is almost 2 times higher than that of 1-dodecylazepan-2-one (Azone; 2.2+/-0.7). From an isopropyl-myristate suspension, the decyl ester was the most effective enhancer (4.9+/-1.4), while Azone was inactive. Decomposition of the carbamate in a slightly acidic environment was shown by FTIR; hydrolysis of the pertinent ester by porcine esterase was monitored by TLC and HPLC. Biodegradable enhancers of this type could mediate easier and faster recovery of the skin barrier after transdermal delivery through the action of the released TXA.
Keywords: Tranexamic Acid; karbamáty; Female; biodegradace; ženské pohlaví; In Vitro Techniques; Esters; vysokoúčinná kapalinová chromatografie; Drug Carriers; aplikace kožní; Skin Absorption; techniky in vitro; lidé; theofylin; Administration, Cutaneous; Spectroscopy, Fourier Transform Infrared; kůže; kožní absorpce; Chromatography, High Pressure Liquid; spektroskopie infračervená s Fourierovou transformací; kyselina tranexamová; Male; Carbamates; Skin; permeabilita; Permeability; nosiče léků; estery; Biodegradation, Environmental; mužské pohlaví; Theophylline; Humans